Using Personal Mobile Devices to increase flexibility and equity in learning in resource constrained contexts. - Cheryl Brown; Genevieve Haupt (Flexible Learning Association of New Zealand, 2018)
This paper examines how in a resource constrained context, access to personal mobile devices for first year university students increases their flexibility of learning and creates a environment of greater inclusivity at University. In 2016, at the start of their first year 201 students in an extended degree program in the Humanities at the University of Cape Town were surveyed about their access to Personal Mobile Devices (PMDs). Based on need, 68 students were given an entry level tablet to use as their own for the duration of their studies.  As a consequence of establishing a learning context where students all had access to a PMD the lecturers could engage students in multimodal blended learning and teaching approach. This paper draws on data in the form of student surveys and focus groups and explores not only the challenges and opportunities for students in using PMDs for their learning both in and out of the classroom but the flexibility of learning enabled through PMDs. The study shows that creating an equitable context in terms of physical access to digital technology enables students' learning but also presents some new challenges.